Kearifan Lokal “Atoni Meto” Sebagai Alternati Penyelesaian Sengketa dalam Menjaga Harmoni Kehidupan Modern - Timoteus Ajito; Augusta De Jesus Magalhaes; Wayan Suja; Made Sutajaya; Ida Bagus Made Astawa; Desak Putu Jeny (Journal on Education, 2024)
Modernization often gives rise to social disputes and crises related to cultural identity. The values ​​of communal unity and harmony that symbolize traditional society are increasingly being replaced by an individualistic and competitive paradigm that ignores the sociocultural dimension. Likewise, the judiciary, which functions as the basis of legal authority, has manifested examples of corruption, collusion and nepotism, thus requiring alternative models for conflict resolution that are efficient, fair and accommodating to the customary law system to maintain the sustainability of customary law communities. This research is primarily oriented towards explaining the implementation of Atoni Meto mediation and rituals as an alternative to resolving disputes outside the court in Kupang Regency, observing the characteristics of case disputes, and exploring the role of local wisdom in mediating Atoni Meto during dispute resolution. The research methodology used is qualitative, including data collection techniques such as observation, interviews and document analysis. The data analysis procedure, as described by Miles and Huberman, includes the phases of data collection, data reduction, data presentation, and formulation and drawing of conclusions. The findings of this research are as follows: 1. Mediation and settlement of peace rituals in Kupang Regency are efforts that do not prioritize justice procedures, because the results cannot only be observed; This model has the potential to realize society's ideals in law, as enshrined in the fifth teaching of Pancasila, which advocates social justice for all Indonesian citizens, thereby framing justice as an integral and holistic moral value; 2. Mediation and the Atoni Meto Ritual as an alternative settlement outside of court are supported not only to avoid the effects of widespread law violations in Indonesia but also because of their sociological acceptance and alignment with local cultural paradigms; 3. Mediation and ritual practices in rescue resolution can be considered as social incentives based on the premise of conflict resolution that avoids favoritism, thereby emphasizing win-win solutions. In the midst of these diverse challenges, local wisdom emerges as a viable solution to maintain balance and harmony in the complexity of modern life.